KARAKTERISTIK PENDERITA SKIZOFRENIA PADA PASIEN RAWAT JALAN DI POLIKLINIK JIWA RSUD H. ANDI SULTHAN DG. RADJA KABUPATEN BULUKUMBA - Hj. Fatmawati; Nurlina (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2019)
Schizophrenia is a severe mental disorder that affects more than 21 million people worldwide. According to (Ministry of Health, 2013) the prevalence of severe mental disorders, such as schizophrenia, is 1.7 per 1000 residents or around 400,000 people. Schizophrenia is caused by multifactorial factors that are related to each other. The purpose of this study was to find out the factors associated with the incidence of mental disorders in H.AUD Hospital. Sulthan with Radja Bulukumba in 2018. This study uses Cross sectional design with a population of 554 people and a sample of 84 people. The sample used in this study is non probability sampling with purposive sampling technique. Based on statistical analysis using frequency distribution data The results of this study are based on the age of Schizophrenia sufferers more in adulthood, the sex of Schizophrenic patients is obtained by men as many as 40 people (50%), and women as many as 40 respondents (50%), Job Schizophrenia sufferers are more unemployed (82.5%) and those who work are 17.5%, the education level of Schizophrenics is higher in high school education (33.8%) and junior and PT education is equal to 13, 8%, The marital status of schizophrenics sufferers with mental disorders is more with marital status (61%), there are more conflicts in families with schizophrenia who do not have a family conflict (85%). Farewell events of Schizophrenia sufferers more than no parents (85%), Socio-economic status of schizophrenics in economic status less than 66 people (82.5%, Parenting schizophrenic parents democratic parenting 75 people or 93.8 %. It is expected that the results of this study may be used as scientific reading material in the library and can also be used as reference material that examines similar problems.